If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-x+3x-2=5x-6-x
We move all terms to the left:
-x+3x-2-(5x-6-x)=0
We add all the numbers together, and all the variables
-x+3x-(4x-6)-2=0
We add all the numbers together, and all the variables
2x-(4x-6)-2=0
We get rid of parentheses
2x-4x+6-2=0
We add all the numbers together, and all the variables
-2x+4=0
We move all terms containing x to the left, all other terms to the right
-2x=-4
x=-4/-2
x=+2
| 47=5t^+2 | | F(x)=8/9-3x | | 7x+7=10x-38=x | | (2+5s)(5)= | | 9x+4=12x-23=x | | x+¼=-¼ | | h^2+6h=160 | | 35=4+5(n+7) | | 1.5p+5.00=14.00 | | -4(1+6f)=30 | | 8x+2=-15-3x | | 8x+2=-15-3 | | 0y-(1y+2)=y | | -=32-5q | | 2(5+9t)= | | 1y-(1y+2)=y | | 15x+4=8x+32 | | 15=9(6h-8) | | 5y+2(3y-1)=y | | -46=-x/5 | | 2(3x-2)=7x+4 | | 35=6x+4x | | 100=4*2*c | | 26=v/4-14 | | 5.3n+725=70.85 | | 6v+7+3=27 | | (9•c)+3=57 | | 4j-9j+3=-34 | | 100=4*2c | | 30+6x+13=9x+7 | | w/2+15=37 | | 7v+v=30 |